2019
DOI: 10.1021/acsabm.9b00768
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Nanostructures with Tunable Donor Loading for Controlled H2S Release

Abstract: Hydrogen sulfide (H 2 S), an endogenously generated and regulated signaling gas, plays a vital role in a variety of (patho)physiological processes. In the past few years, different kinds of H 2 S-releasing compounds (often referred to as H 2 S donors) have been developed for H 2 S delivery, but it is still challenging to make H 2 S donors with tunable payloads in a simple and efficient manner. Herein, a series of peptide-H 2 S donor conjugates (PHDCs) with tunable donor loadings are designed for controlled H 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…This is consistent with previous CAC measurements on similar APAs. 18,29,39,40 CD spectroscopy revealed that the secondary structures of these peptide nanoassemblies were similar, and both displayed strong signals in the peptide region (190-240 nm) and in the SATO characteristic absorption region (300-360 nm), consistent with SATO absorptions in the corresponding UV−vis spectra (Fig. S6).…”
Section: Effect Of Salt Concentration On Molecular Packingsupporting
confidence: 57%
“…This is consistent with previous CAC measurements on similar APAs. 18,29,39,40 CD spectroscopy revealed that the secondary structures of these peptide nanoassemblies were similar, and both displayed strong signals in the peptide region (190-240 nm) and in the SATO characteristic absorption region (300-360 nm), consistent with SATO absorptions in the corresponding UV−vis spectra (Fig. S6).…”
Section: Effect Of Salt Concentration On Molecular Packingsupporting
confidence: 57%
“…To make the PHDCs, we prepared a peptide of the structure AdK S K S EE (Ad = adamantyl group, K S = lysine residue functionalized with an H 2 S-releasing S -aroylthiooxime (SATO) group, E = glutamic acid residue; Figure A). We originally developed the SATO group because of its ability to generate H 2 S in response to thiols, but we found that its inclusion in peptides generates a variety of self-assembled morphologies; for example, PHDCs containing two K S and two E residues form persistent nanohelices or nanoribbons of various sizes depending on the specific sequence. Here, we included for the first time the bulky Ad group with the idea that it would provide additional hydrophobic interactions beyond those of the SATO groups, while also contributing steric hindrance during the self-assembly process. Detailed synthetic procedures and characterization can be found in the Supporting Information (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Among the classes of synthetic small molecules capable of self-assembly into nanostructures, peptides are perhaps the most widely studied because of their biodegradability, high degree of tunability, and capacity for several types of noncovalent interactions. ,, Beyond this, they can be quickly synthesized and purified with direct sequence control. Our group is interested in the aqueous self-assembly of short peptides and peptide derivatives into unusual nanostructures and their applications in biology and other areas. Here, we report on our recent discovery of an aromatic peptide amphiphile that self-assembles into crescent-shaped nanostructures. Crescent-shaped inorganic nanostructures have been prepared through various means, and their crescent shape affords unique properties. In contrast, it remains a great challenge to produce crescent nanostructures from peptides, or any small organic molecule, through a direct self-assembly approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart and selective therapeutic approaches derived from stimuli-responsive peptide-based hydrogels invite immense interest from diverse segments of science. Cost-effectiveness, biocompatibility, control over structural diversity, and involvement of noncovalent interactions have propelled the idea of harnessing the process of self-assembly of peptides for tackling various aspects related to biomedical applications. Commonly, the stimuli that nucleate the self-assembly phenomena are heat, light, pH, ionic strength, ultrasound, enzymes, and others. However, these stimuli often take the back seat as they hamper the inherent properties of the molecules due to the utilization of high energy or foreign chemicals. However, exploration of mechanoresponsive hydrogels still remains in its infancy. In particular, mechanoresponsive (thixotropic) hydrogels are advantageous over others owing to the ease of sol–gel transition commenced simply through mechanical force initiation .…”
Section: Introductionmentioning
confidence: 99%